A Road Damage Analysis Using the Bina Marga Method (A Case Study of the Tapung–Tandun Road, STA 0+000 – STA 5+000, Kampar Regency, Riau Province - Abdul Kudus Zaini; Fachrurrozi Fachrurrozi; Muchammad Zaenal Muttaqin; Sy Sarah Alawiyah (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
The Tapung–Tandun road is a provincial highway that links Tapung District and Tandun region. This road falls under the classification of a third-class collector road, spanning 45.5 kilometers in length and featuring a 7-meter-wide carriageway. As transportation demands continue to rise on the Tapung–Tandun road, the increased vehicular traffic has not been met with commensurate infrastructure, leading to substantial surface damage. The objectives of this study were to determine the types of damage present on the flexible pavement of the Tapung–Tandun road, to evaluate the extent of road damage using the Bina Marga method, and to ascertain the average daily traffic flow along the Tapung–Tandun road. The method employed to analyze road damage on the Tapung–Tandun road was the Bina Marga method. The results of the road damage survey on this road in Kampar Regency revealed various types of damage, including cracks, potholes, aggregate loss, and rutting. The analysis of road damage using the Bina Marga method yielded the following percentages of damage: 3.748% for cracking from STA 0+000 to STA 5+000, 4.573% for potholes from STA 0+000 to STA 5+000, 5.848% for aggregate loss from STA 0+000 to STA 5+000, and 2.537% for rutting from STA 0+000 to STA 5+000. The analysis using the Bina Marga method determined a road maintenance program level of 3, indicating that the Tapung–Tandun road fell under the category of road improvement programs. The survey results for the average daily traffic (ADT) volume indicated a total of 5,113 PCU/day. Among various vehicle types, sedans, jeeps, and station wagons were the most prevalent on the Tapung–Tandun road, with a total of 2,029 PCU/day, while trucks with 4 axles (1.2-2.2) or trailers were the least common, with 27 PCU/day.